Pemberdayaan Masyarakat Melalui Program Masjid Literasi “Rumah Literasiku” - Uswatun Hasanah (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This report of community service (PkM) discusses community service in the form of a library facility namely